Peran Badan Pengawas Pemilihan Umum dalam Pemberantasan Politik Uang Di Kabupaten Minahasa - Paseki, Dicky Janeman; Pinasang, Boby; Taroreh, Hironimus (Nuansa Akademik: Jurnal Pembangunan Masyarakat, 2024)
The aim of the research is limited to legal efforts that can be carried out by the General Election Supervisory Agency to eradicate money politics in Minahasa Regency. Normative legal research methods utilize case approaches and legislation. Literature study in the form of legal materials as well as interviews and observations of data collection tools. Research results show that Bawaslu has the task of preventing and taking action against elections, as well as election process disputes in accordance with Article 93 letter b of Law Number 7 of 2017 concerning Elections. Bawaslu is even closer if it is said to be active in the process of upholding election justice related to preventing money politics.